1996
DOI: 10.1007/bf02337514
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial DNA molecule of sumatran orangutan and a molecular proposal for two (Bornean and Sumatran) species of orangutan

Abstract: The complete mitochondrial DNA (mtDNA) molecule of Sumatran orangutan, plus the complete mitochondrial control region of another Sumatran specimen and the control regions and five protein-coding genes of two specimens of Bornean orangutan were sequenced and compared with a previously reported complete mtDNA of Bornean orangutan. The two orangutans are presently separated at the subspecies level. Comparison with five different species pairs-namely, harbor seal/grey seal, horse/donkey, fin whale/blue whale, comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 27 publications
2
75
0
Order By: Relevance
“…In addition to ND5 data, orangutan DNA sequences from other mitochondrial regions have been previously reported (Ruvolo et al 1994;Xu and Arnason 1996a;Zhi et al 1996;Muir et al 2000). Here we also reanalyzed 16s rRNA data from Zhi et al (1996) (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ND5 data, orangutan DNA sequences from other mitochondrial regions have been previously reported (Ruvolo et al 1994;Xu and Arnason 1996a;Zhi et al 1996;Muir et al 2000). Here we also reanalyzed 16s rRNA data from Zhi et al (1996) (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies of chromosomes, proteins, DNA hybridization, mtDNARFLPs, mtDNA sequences, minisatellites, etc., have demonstrated that the genetic differences between the two orangutans are almost the same as or even higher than those of other putative species like chimpanzee/ bonobo, horse/donkey, etc. (Bruce and Ayala 1979;Ferris et al 1981;Caccone and Powell 1989;Janczewski et al 1990;Ryder and Chemnick 1993;Xu and Arnason 1996a;Zhi et al 1996;Muir et al 2000). Based on these differences, some researchers have suggested that the two orangutans should be elevated to be separate species (Xu and Arnason 1996a).…”
Section: Taxonomic Status Of the Two Orangutansmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] de Vos 22,23 has argued that the Indonesian paleoenvironmental record reveals a more recent divergence, while Harrison et al 15 hypothesized that orangutans dispersed into Sundaland during a cold phase in the late Pliocene (~2.7 mya) and fragmented at the start of the Pleistocene (~1.8 mya), becoming genetically distinct subsequent to this. Unfortunately little is known about the biogeography of Early Pleistocene orangutans, due in part to the limited fossil record, lack of securely dated sites, and ambiguity regarding the taxonomic identification of primate material.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last twenty years there have been debates over the specific status of Sumatran (Pongo abelii) and Bornean orangutans (Pongo pygmaeus) (Groves 1986;Hobolth, Dutheil, et al 2011;Xu and Arnason 1996), based primarily on genomic data (Locke, Hillier, et al 2011). For most of the twentieth century, primatologists identified one orangutan species (P. pygmaeus) and several subspecies.…”
Section: Using Snarcs In Systematic Evolutionary and Ecological Stumentioning
confidence: 99%